Nucleosome proteostasis and histone turnover - Arrieta, Adrian; Vondriska, Thomas M. (Frontiers in Molecular Biosciences, 2022)
Maintenance of protein folding homeostasis, or proteostasis is critical for cell survival as well as for execution of cell type specific biological processes such as muscle cell contractility, neuronal synapse and memory formation, and cell transition from a mitotic to post-mitotic cell type. Cell type specification is driven largely by chromatin organization, which dictates which genes are turned off or on, depending on cell needs and function. Loss of chromatin organization can have catastrophic consequences either on cell survival or cell type specific function. Chromatin organization is highly dependent on organization of nucleosomes, spatiotemporal nucleosome assembly and disassembly, and histone turnover. In this review or goal is to highlight why nucleosome proteostasis is critical for chromatin organization, how this process is mediated by histone chaperones, and outline potential and established mechanisms of disrupted nucleosome proteostasis during disease. Finally, we highlight how these mechanisms of histone turnover and nucleosome proteostasis may conspire with unfolded protein response programs to drive histone turnover in cell growth and development.